The performance of the Egyptian export economy in the open-door period - Baroudi, Sami E. (1992)
This study focuses on explaining what caused the deterioration in the real terms value of Egypt's agricultural exports, during the open‑door period. It evaluates alternative hypotheses on the probable cause of such deterioration. H‑1 attributes the deterioration in exports to the lack of significant growth in the size of Egypt's cultivated area. H‑2 attributes the deterioration in exports to government policy which denied the private export community, in agriculture, complete and free direct access to the international agricultural markets. The comparative evaluation of H‑1 and H‑2 reveals the latter to be far superior to the former. H‑2 can, nevertheless, be challenged on three principal grounds. The first challenge to H‑2 can be expressed as an alternative hypothesis H‑3. H‑3 attributes the deterioration in agricultural exports to the intensification of protectionism tendencies in the Northern markets. Our examination of the conditions of entry granted to Egypt's agricultural exports in Northern markets reveals that H‑3 does a very poor job in explaining why the deterioration in agricultural exports occurred. The second and third challenges to H‑2 focus, respectively, on the problematic performance of the private sector in the horticultural export sphere, and on the political obstacles that would have prevented the adoption of a policy of completely freeing private sector access to the international agricultural markets. Our examination of both challenges shows them to be of limited validity. The conclusion extends the argument about the critical importance of government policy to the industrial exports sphere.